2003
DOI: 10.1046/j.1439-0450.2003.00681.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Mycoplasmas from Nasal Swabs of Calves affected with Respiratory Diseases and Antimicrobial Susceptibility of their Isolates

Abstract: Nasal swabs of 293 calves were examined for Mycoplasma. The samples were collected from calves affected with respiratory diseases on 71 farms in various parts of Japan between 1996 and 1997. Mycoplasma bovirhinis was isolated from 47 of 293 calves (16.0%). Mycoplasma alkalescens, M. bovis, M. arginini, M. bovigenitalium and Acholeplasma spp. were isolated from 19 (6.5%), seven (2.4%), four (1.4%), four (1.4%) and 18 (6.1%) calves, respectively. Pasteurella multocida and P. haemolytica were isolated from 60% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 17 publications
6
44
3
Order By: Relevance
“…M. dispar and M. arginini were the next bacteria frequently encountered in our research. The first pathogen plays the primary role in infection, and the second one is regarded as an opportunist, being isolated rather rarely and mainly in co-infections with M. bovis (5,9). U. diversum and M. canis are also significant in cattle respiratory diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…M. dispar and M. arginini were the next bacteria frequently encountered in our research. The first pathogen plays the primary role in infection, and the second one is regarded as an opportunist, being isolated rather rarely and mainly in co-infections with M. bovis (5,9). U. diversum and M. canis are also significant in cattle respiratory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Usually the disease is associated with other pathogenic microorganisms such as viruses and other bacteria (8,18). Other mycoplasmas including M. dispar, M. canis, M. arginini, and the related species U. diversum have been directly implicated in BRD (5,9,18). Moreover, other mycoplasma species such as M. alkalescens, M. canadense, and M. bovirhinis are involved in cattle respiratory infection (13,18,25).…”
Section: Introductionmentioning
confidence: 99%
“…This species causes disruption of normal ciliary function in the tracheal epithelium and predisposes the lower respiratory tract to infection with primary lung pathogens. M. dispar is frequently isolated from 3-4 month-old calves with respiratory diseases; however, it may also be detected in healthy animals (Hirose et al 2003, Marques et al 2007. Some of these species are often found as a part of the microbial flora of the upper respiratory tract in healthy calves, and in most reports they have been isolated in mixed infections with other known pathogens .…”
Section: Introductionmentioning
confidence: 99%
“…Infrequent or no resistance has been reported to enrofloxacin or florfenicol (Francoz et al, 2005, Gerchman et al, 2009, Hirose et al, 2003, Rosenbusch et al, 2005, Siugzdaite et al, 2012. Successful treatment of M. bovis pneumonia and arthritis in calves using valnemulin in the milk from four days of age for three weeks has also been reported (Stipkovits et al, 2001).…”
Section: Disease Prevention and Controlmentioning
confidence: 99%
“…In addition, in the past decade, in vitro susceptibility studies have shown an increased resistance to antimicrobials commonly used to treat infections associated with M. bovis; in particular oxytetracyclines, spectinomycin, tilmicosin and chlortetracycline (Francoz et al, 2005, Gerchman et al, 2009, Hirose et al, 2003, Rosenbusch et al, 2005, Siugzdaite et al, 2012. Infrequent or no resistance has been reported to enrofloxacin or florfenicol (Francoz et al, 2005, Gerchman et al, 2009, Hirose et al, 2003, Rosenbusch et al, 2005, Siugzdaite et al, 2012.…”
Section: Disease Prevention and Controlmentioning
confidence: 99%